CONTROL A SMALL WIND TURBINE WITH ASYNCHRONOUS GENERATOR - Możdżyński, Kamil; Gajowik, Tomasz; Rafał, Krzysztof; Malinowski, Mariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The article presents the control system wind turbine with asynchronous squirrel cage generator with a capacity of 11 kW. Asynchronous generator compared to the synchronous generator characterized by a lower cost and higher reliability, but because of the phenomena associated with excitation, it is necessary to use a more complex system of the converter and an additional devices supporting the operation of the wind power plant under realistic conditions. As a result, control of the power electronic inverter coupling generator with power grid requires additional expand on the ability to manage the entire power plant. The article discusses the issues and experimental results related to the states of the system of small wind power plant and process control loops of power processing.